Evaluating the Treatment of Diabetic Macular Edema with Aflibercept Based on a Regional Network of Ophthalmologic Care Givers. (10th January 2023) - Khalil, Haidar; Mariacher, Siegfried; Strauss, Rupert; Podkowinski, Dominika; Waser, Klemens; Bolz, Matthias
Abstract : Purpose . In Austria, anti-VEGF therapies are reimbursed only in clinical settings. This study aimed to describe the outcome of a treat and extend regimen (TER) with aflibercept for diabetic macular edema (DME) in a network of practitioners. Methods . In a prospective study over 36 months, patients with DME were treated with a loading dose of aflibercept and further on with adjusted treatment intervals based on optical coherence tomography (OCT) findings. All patients were monitored in an outpatient setting by regional ophthalmologists, and the treatment was administered in the clinic. Main outcome parameters were best-corrected visual acuity (BCVA) from baseline to the last regular visit. Number of visits at the practitioner's office as well as the number of injections were secondary outcome parameters. Results . Thirty-three patients completed the study at their final visit. BCVA improved significantly by 5.8 letters between baseline and the final visit from 70.4 letters at baseline (p = 0.004 ). Patients visited the practitioner's office 12.8 times in the observation period of 36 months. 3.7, 5.1, and 3.9 visits were performed, respectively, in the first, second, and third years, and 25.5 ± 7.9 injections were performed. The mean interval of injections over the observation period was 6.2 ± 2.2 in weeks. Conclusion . The treat and extend regimen was valuable for treating patients with DME in this specific setting. The functional results of this study were comparable to those of other real-world evaluations. Adherence to the same treating institution seems to be important to avoid differences in therapeutic decision making and may also increase patient's compliance.